Identification of Lactic Acid Bacteria in Fruit Pulp Processing Byproducts and Potential Probiotic Properties of Selected Lactobacillus Strains - Garcia, Estefânia F.; Luciano, Winnie A.; Xavier, Danilo E.; da Costa, Whyara C. A.; de Sousa Oliveira, Kleber; Franco, Octávio L.; de Morais Júnior, Marcos A.; Lucena, Brígida T. L.; Picão, Renata C.; Magnani, Marciane; Saarela, Maria; de Souza, Evandro L. (Frontiers in Microbiology, 2016)
This study aimed to identify lactic acid bacteria (LAB) in byproducts of fruit (Malpighia glabra L., Mangifera indica L., Annona muricata L. and Fragaria vesca L.) pulp processing. Fifty strains of LAB were identified using matrix-assisted laser desorption/ionization–time of flight mass spectrometry (MALDI-TOF MS) and 16S rRNA gene sequence (16S rRNA) analysis. Species belonging to Lactobacillus genus were the predominant LAB in all fruit pulp processing byproducts. The average congruency between the MALDI-TOF MS and 16S rRNA in LAB species identification reached 86%. Isolates of L. plantarum, L. brevis, L. pentosus, L. lactis and L. mesenteroides were identified with 100% congruency. MALDI-TOF MS and 16S rRNA analysis presented 86% and 100% efficiency of LAB species identification, respectively. Further, five selected Lactobacillus strains (L. brevis 59, L. pentosus 129, L. paracasei 108, L. plantarum 49 and L. fermentum 111) were evaluated for desirable probiotic-related properties and growth behavior on two different cultivation media. The exposure to pH 2.0 sharply decreased the counts of the different Lactobacillus strains after a 1 or 2 h incubation, while varied decreases were noted after 3 h of exposure to pH 3.0. Overall, the exposure to pH 5.0 and to bile salts (0.15, 0.30 and 1.00%) did not decrease the counts of the Lactobacillus strains. All tested Lactobacillus strains presented inhibitory activity against Staphylococcus aureus, Salmonella Typhimurium, Salmonella Enteritidis, Listeria monocytogenes and Escherichia coli, and presented variable susceptibility to different antibiotics. The selected Lactobacillus strains presented satisfactory and reproducible growth behavior. In conclusion, MALDI-TOF MS and 16S rRNA analysis revealed high efficiency and congruency for LAB species identification, and the selected Lactobacillus strains may be candidates for further investigation of novel probiotic strains.